2017
DOI: 10.21726/rsbo.v1i1.387
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of vertical maxillary excess associated with mandibular self-rotation

Abstract: Introduction: The Class I skeletal deformity associated with vertical maxillary excess is a rare condition reported in the literature. Surgical impaction allows the correction of the long face and gummy smile. Objective: This case report aimed to evaluate the positioning of the condyle after Le Fort I osteotomy associated with mandibular selfrotation. Case report: The patient underwent orthognathic surgery for the correction of maxillary vertical excess. Tomography studies were performed to evaluate the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Clinically, VME is categorized according to the presence or absence of anterior open bite. 10 In this case the treatment protocol adopted is the nonextraction treatment modality with surgical mandibular advancement for the correction of underlying mandibular hypoplasia. In the above case maxilla was normal both in sagittal as well as in the transverse plane, but the mandible was deficient in the sagittal plane with increased vertical vector.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, VME is categorized according to the presence or absence of anterior open bite. 10 In this case the treatment protocol adopted is the nonextraction treatment modality with surgical mandibular advancement for the correction of underlying mandibular hypoplasia. In the above case maxilla was normal both in sagittal as well as in the transverse plane, but the mandible was deficient in the sagittal plane with increased vertical vector.…”
Section: Discussionmentioning
confidence: 99%
“…The lower third of the face is long, leading to a retrognathic shape of the jaw. 17 Furthermore, the incisal edge of the upper anterior teeth might be covered by the lower lip because of the extravagant downward growth of the maxilla. 16 Peck et al, 9 and Mackley 18 found that a Gummy Smile is highly related to anterior vertical maxillary excess (about 2-3 mm).…”
Section: Vertical Maxillary Excessmentioning
confidence: 99%
“…35 The Le Fort I osteotomy of the maxilla allows reduction of bone between the nasal floor and apices of maxillary teeth which permits superior repositioning (impaction) of the maxilla. 17 When having bimaxillary protrusion, the treatment option may be composed of first premolar extractions followed by the osteotomy through the extraction sites to mobilize the anterior segment of the maxilla. The aim is to setback the segment in addition to lessening the labial flaring of the incisors.…”
Section: Treatment Of Gummy Smilementioning
confidence: 99%
“…This is known as a gummy smile, and about 10% of the population between 20 and 30 years of age present excessive gingival display, which is more prevalent in women [1][2]. 7% of the 10% gingival exposure self-reduces by forceful closure of the upper and lower lip by reducing incisor display [3].…”
Section: Introductionmentioning
confidence: 99%